OP0295-HPR Increasing Physical Activity in Ankylosing Spondylitis (Inpact-as): A Randomised Controlled Trial. (15th July 2016) - O'Dwyer, T.; Monaghan, A.; Moran, J.; Wilson, F.; O'Shea, F.
Abstract : Background: The numerous benefits of physical activity (PA) are well established, and guidelines recommend adults obtain ≥150 minutes of moderate-intensity PA per week in bouts lasting ≥10 minutes (PABOUTS ) 1 . PA, including exercise, is a key component of the management of ankylosing spondylitis (AS), however participation in PA in this cohort is low 2, 3 . Objectives: The INPACT-AS trial explored the effects of a PA behaviour change intervention on habitual PA of adults with AS; secondary aims explored effects on spinal mobility and AS-related features. Methods: This single-blind, parallel-group randomised controlled trial recruited adults diagnosed with AS. Exclusion criteria were the presence of comorbidities limiting PA, or recent changes in medication usage. Forty participants (26 males) were randomised to an intervention group (IG) or a control group (CG). Over a 12-week period, the IG had individual consultations with a physiotherapist, aiming to optimise habitual PA. The CG continued with 'usual care'. Blinded outcome assessments were conducted at baseline, post-intervention, and 12-week follow-up. Habitual PA was measured during waking hours with ActiGraph GT3x accelerometers. Questionnaires administered included the Bath AS Disease Activity Index, Bath AS Functional Index, and the AS Quality of Life questionnaire (ASQoL). The Bath AS Metrology Index (BASMI) measured spinal mobility. An intention-to-treat analysis was performed. Results: Mean (SD) age was 38.9 (7.6) years in the IG and 44.8 (9.7) years in the CG. Mean symptom duration was 17.7 (9.5) years in the IG and 24.4 (13.6) years in the CG. Other baseline socio-demographic, AS, medication, and PA-related features were similar across groups ( p >0.05). No adverse effects were reported during the study. Median number of IG consultations was 5 (IQR 1). Post-intervention, there were significant between-group differences in health-related PA, of large effect size (Tab. 1). After follow-up, significantly more participants in the IG met PA guidelines than in the CG [χ 2 (1)=12.379, p <0.0005] (Fig. 1 ). BASMI score changes significantly favoured the IG [ANOVA: F (2, 76)=5.691, p =0.005]. ASQoL scores significantly improved in the IG [Friedman's test, χ 2 (2)=8.400, p =0.015]. Conclusions: This was the first behaviour change intervention targeting PA in an AS cohort. Health-enhancing PA, spinal mobility and quality of life were significantly improved after the intervention, and improvements were maintained at three-month follow-up. References: WHO. Global recommendations on physical activity for health. Geneva, Switzerland: WHO, 2010 Millner JR, et al. (2015) Exercise for ankylosing spondylitis: an evidence-based consensus statement. Semin Arthritis and Rheum. [epub] O'Dwyer T, et al. (2015) Decreased physical activity and cardiorespiratory fitness in adults with ankylosing spondylitis. Rheumatol Int. 35:1863–72 Disclosure of Interest: None declared